Palladium-catalyzed ortho-halogenations of acetanilides with N-halosuccinimides via direct sp2 C–H bond activation in ball mills - Liu, Zi; Xu, Hui; Wang, Guan-Wu (Beilstein Journal of Organic Chemistry, 2018)
A solvent-free palladium-catalyzed ortho-iodination of acetanilides using N-iodosuccinimide as the iodine source has been developed under ball-milling conditions. This present method avoids the use of hazardous organic solvents, high reaction temperature, and long reaction time and provides a highly efficient methodology to realize the regioselective functionalization of acetanilides in yields up to 94% in a ball mill. Furthermore, the current methodology can be extended to the synthesis of ortho-brominated and ortho-chlorinated products in good yields by using the corresponding N-halosuccinimides.
Keywords: acetanilide; ball milling; C–H activation; halogenation; mechanochemistry; N-halosuccinimide; palladium catalysis

(untitled) - Evans, D. A.; Katz, J. L.; Peterson, G. S.; Hintermann, T. (J. Am. Chem. Soc., 2001)

U.S. Patent - Pelletier, J. C.; Youssefyeh, R. D.; Campbell, H. F. (Substituted Saturated and Unsaturated Indole Quinoline and Benzazepine Carboxamides and Their Use as Pharmacological Agents, 1990)

Electrophilic Halogenation - de la Mare, P. B. D. (Cambridge University Press, 1976)

(untitled) - Hodgson, H. H. (Chem. Rev., 1947)

(untitled) - Kalyani, D.; Dick, A. R.; Anani, W. Q.; Sanford, M. S. (Org. Lett., 2006)

(untitled) - Bedford, R. B.; Haddow, M. F.; Mitchell, C. J.; Webster, R. L. (Angew. Chem., Int. Ed., 2011)

(untitled) - Dubost, E.; Fossey, C.; Cailly, T.; Rault, S.; Fabis, F. (J. Org. Chem., 2011)

(untitled) - Schröder, N.; Wencel-Delord, J.; Glorius, F. (J. Am. Chem. Soc., 2012)

(untitled) - John, A.; Nicholas, K. M. (J. Org. Chem., 2012)

(untitled) - Ma, X.-T.; Tian, S.-K. (Adv. Synth. Catal., 2013)

(untitled) - Zhao, X.; Dimitrijević, E.; Dong, V. M. (J. Am. Chem. Soc., 2009)

(untitled) - Wang, W.; Pan, C.; Chen, F.; Cheng, J. (Chem. Commun., 2011)

(untitled) - Mei, T.-S.; Giri, R.; Maugel, N.; Yu, J.-Q. (Angew. Chem., Int. Ed., 2008)

(untitled) - Mei, T.-S.; Wang, D.-H.; Yu, J.-Q. (Org. Lett., 2010)

(untitled) - Li, J.-J.; Mei, T.-S.; Yu, J.-Q. (Angew. Chem., Int. Ed., 2008)

(untitled) - Wan, X.; Ma, Z.; Li, B.; Zhang, K.; Cao, S.; Zhang, S.; Shi, Z. (J. Am. Chem. Soc., 2006)

(untitled) - Bedford, R. B.; Engelhart, J. U.; Haddow, M. F.; Mitchell, C. J.; Webster, R. L. (Dalton Trans., 2010)

(untitled) - Song, B.; Zheng, X.; Mo, J.; Xu, B. (Adv. Synth. Catal., 2010)

(untitled) - Stolle, A.; Szuppa, T.; Leonhardt, S. E. S.; Ondruschka, B. (Chem. Soc. Rev., 2011)

(untitled) - James, S. L.; Adams, C. J.; Bolm, C.; Braga, D.; Collier, P.; Friščić, T.; Grepioni, F.; Harris, K. D. M.; Hyett, G.; Jones, W.; Krebs, A.; Mack, J.; et al. (Chem. Soc. Rev., 2012)

(untitled) - Zhu, S.-E.; Li, F.; Wang, G.-W. (Chem. Soc. Rev., 2013)

(untitled) - Wang, G.-W. (Chem. Soc. Rev., 2013)

(untitled) - Do, J.-L.; Friščić, T. (ACS Cent. Sci., 2017)

(untitled) - Hernández, J. G.; Bolm, C. (J. Org. Chem., 2017)

(untitled) - Achar, T. K.; Bose, A.; Mal, P. (Beilstein J. Org. Chem., 2017)

(untitled) - Hernández, J. G. (Chem. – Eur. J., 2017)

(untitled) - Bose, A.; Mal, P. (Tetrahedron Lett., 2014)

(untitled) - Maiti, S.; Mal, P. (Synth. Commun., 2014)

(untitled) - Juribašić, M.; Užarević, K.; Gracin, D.; Ćurić, M. (Chem. Commun., 2014)

(untitled) - Hernández, J. G.; Bolm, C. (Chem. Commun., 2015)

(untitled) - Hermann, G. N.; Becker, P.; Bolm, C. (Angew. Chem., Int. Ed., 2015)

(untitled) - Hermann, G. N.; Becker, P.; Bolm, C. (Angew. Chem., Int. Ed., 2016)

(untitled) - Lou, S.-J.; Mao, Y.-J.; Xu, D.-Q.; He, J.-Q.; Chen, Q.; Xu, Z.-Y. (ACS Catal., 2016)

(untitled) - Hermann, G. N.; Bolm, C. (ACS Catal., 2017)

(untitled) - Hermann, G. N.; Jung, C. L.; Bolm, C. (Green Chem., 2017)

(untitled) - Jia, K.-Y.; Yu, J.-B.; Jiang, Z.-J.; Su, W.-K. (J. Org. Chem., 2016)

(untitled) - Jiang, X.; Chen, J.; Zhu, W.; Cheng, K.; Liu, Y.; Su, W.-K.; Yu, C. (J. Org. Chem., 2017)

(untitled) - Cheng, H.; Hernández, J. G.; Bolm, C. (Org. Lett., 2017)

(untitled) - Li, L.; Wang, J.-J.; Wang, G.-W. (J. Org. Chem., 2016)

(untitled) - Li, H.-G.; Wang, G.-W. (J. Org. Chem., 2017)

(untitled) - Xu, H.; Liu, H.-W.; Lin, H.-S.; Wang, G.-W. (Chem. Commun., 2017)

(untitled) - Wang, G.-W. (Top. Organomet. Chem., 2016)

(untitled) - Wang, G.-W.; Yuan, T.-T.; Li, D.-D. (Angew. Chem., Int. Ed., 2011)

(untitled) - Li, Z.-Y.; Li, L.; Li, Q.-L.; Jing, K.; Xu, H.; Wang, G.-W. (Chem. – Eur. J., 2017)

(untitled) - Boele, M. D. K.; van Strijdonck, G. P. F.; de Vries, A. H. M.; Kamer, P. C. J.; de Vries, J. G.; van Leeuwen, P. W. N. M. (J. Am. Chem. Soc., 2002)